Expression of miR-146a, miR-155, and miR-223 in formalin-fixed paraffin-embedded synovial tissues of patients with rheumatoid arthritis and osteoarthritis - Kriegsmann, Mark; Randau, Thomas M.; Gravius, Sascha; Kriegsmann, Katharina; Altmann, Carolin; Arens, Norbert; Kriegsmann, Jörg (Virchows Archiv, 2016)
Rheumatoid arthritis (RA) is a chronic autoimmune disease with a heterogeneous clinical presentation affecting about 1 % of adults in developed countries. Currently, the diagnosis is based on the revised criteria of the American College of Rheumatology (ACR) and the European League Against Rheumatism (EULAR) from 2010. These criteria include clinical and laboratory parameters. Because of the variability of the clinical picture, delayed diagnosis of RA occurs in a significant subset of patients. Therefore, the discovery of novel biomarkers that improve the diagnosis of RA is of particular interest. Recently, it became evident that miRNAs have regulatory activities in physiologic processes and human diseases. Upregulation of miR-146a, miR-155, and miR-223 has been shown in various compartments such as serum, blood, synovial fluid, and tissues in patients with RA. A total of 87 samples were analyzed (RA 50, osteoarthritis (OA) 37). RNA was isolated from formalin-fixed paraffin-embedded synovial tissue (FFPE). The relative expression of miR-146a, miR-155, and miR-223 was determined by comparison to a housekeeping RNA molecule (snRNA U6) and an RNA pool from histologically and clinically verified OA samples. miR-146a, miR-155, and miR-223 were significantly elevated in RA compared to OA synovial tissues (p < 0.001). A strong correlation between the miRNAs could be observed. The sensitivity and specificity for the detection of RA were 0.76/0.80 (miR-146a), 0.80/0.95 (miR-155), and 0.86/0.81 (miR-223). The combination of miR-155 and miR-223 resulted in the highest area under the curve (AUC 0.92) with a sensitivity and specificity of 0.84/0.91, respectively. Significantly higher expression levels of miR-146a, miR-155, and miR-223 in FFPE synovial tissue samples of patients with established RA compared to patients with OA were shown. The usefulness of these miRs for the differential diagnosis of early phases of RA against OA remains to be investigated.
Gesehen am 28.05.2020